PENGARUH PENERAPAN METODE LISTENING TEAM DISERTAI HANDOUT TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X MAN KOTO BERAPAK BAYANG PESISIR SELATAN TAHUN PELAJARAN 2013/2014 - Oktaria, Yespi - (Pendidikan Biologi, 2014)
This research is motivated biology by students low yields, lack of biology resources and learning process is still based on the teacher. The method that can be applied to improve students learning outcomes is Listening Team Method with Handout. This research aims to determinate the effect of Listening Team Method with Handout application for biology student X grade MAN Koto Berapak Bayang Pesisir Selatan Tahun Pelajaran 2013/2014 outcomes. Type of this research with Randomized Control Group Post-test Only Design. Population in this research is entired students X MAN Koto Berapak. The sampling technique is purpossive sampling. Eksperimental class X2 and control class is X4. Instrument in this research is objective matter with five option. Average of experiment class students outcomes is 74,33 and control class students is 62,46. Based on the result t-test at the 0,05 significante level tobtained = 2,93 and ttable = 1,67. Means H1 accepted. It means that the application of Listening Team Method with Handout is able to improve biology students learning outcomes.